Mechanical and surface analysis of Ti0.4Al0.6N/Mo multilayers - Tavares, C. J. (2001)
The quest for hard materials that are able to sustain elevated stresses as tools or cutting processes has led to the investigation of (Ti,Al)N/Mo multilayer coatings. These structures have been deposited by dc magnetron sputtering on high-speed steel and stainless-steel substrates and designed with modulation periods of approximately 13 nm, up to a total thickness of 2.8 [mu]m. Experimental X-ray diffraction (XRD) achieved the basics involving structural quality and texture while RBS provided the composition. From AFM observations the waviness of the surface was monitored and it was found that the rms roughness values were minimised for a bias voltage of -120 V. Ultramicrohardness values of 33 GPa were obtained for the best samples, and their adhesion to the steel substrates was also studied. Residual stress measurements revealed a compressive stress state that prevailed in these structures, ranging from -0.2 to -1.3 GPa.